Ability to Recognize Pattern Concepts through Loose Parts Media for 4-5 Year Old Children - Asriadi AM, Muh; Syahrini (Jurusan PG-PAUD Universitas Halu Oleo,, 2024)
This study explores the effect of loose parts media on improving pattern recognition in 4-5-year-olds at Nusa Indah Kindergarten, motivated by the need to find innovative approaches to enhance early childhood education. Early recognition of patterns is a fundamental cognitive skill that supports later academic learning, particularly in mathematics and literacy. Therefore, the objective of this research is to determine the effectiveness of loose parts media in fostering the development of pattern recognition skills among young children. The study employs a descriptive qualitative approach, gathering data through interviews with teachers and documentation of classroom activities. The results indicate that the use of loose parts media, which involves natural or everyday objects that children can manipulate, significantly enhances their ability to recognize and create patterns. The children engaged more deeply with the learning material, demonstrated improved focus, and exhibited a higher level of creativity in their responses. The study concludes that incorporating loose parts media into early childhood education provides a more interactive and effective method for addressing challenges related to pattern recognition. It also suggests that such media can make learning more enjoyable and meaningful, thereby fostering a positive attitude towards learning in young children. This research offers valuable insights for educators, emphasizing the importance of adopting innovative and child-centered teaching strategies to enhance cognitive development in early learners.